Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Les paradoxes des droits reproductifs au Brésil: avortement et stérilisation féminine - Scavone, Lucila; Bateman, Simone; Le Doaré, Hélène (Cahiers du Genre, 1999)
Cet article rend compte du débat mené au Brésil autour des droits reproductifs et souligne les avancées et les contradictions particulières de deux problèmes que rencontrent actuellement les femmes brésiliennes : la stérilisation et la pratique illégale de l’avortement. Il met en évidence que la pratique généralisée de la stérilisation féminine et le nombre des avortements clandestins, qui représentent un risque pour la santé des femmes, révèlent les carences de la politique de la santé sur le plan des choix reproductifs et de la politique de contrôle démographique. Il montre les diverses orientations prises par ce débat à la fin des années quatre-vingt-dix et la nécessité de se réapproprier sa dynamique de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du sud; approches et analyses; brésil; corps; cours; discipline; discours dominant; droits des femmes*; justice reproductive; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Techniques et acteurs: parcours différenciés de femmes dans une démarche de fécondation in vitro - Tain, Laurence (Cahiers du Genre, 1999)
L’analyse des relations entre acteurs des nouvelles techniques de reproduction a souvent conduit à privilégier la description des stratégies de ceux qui sont désignés comme dominants : les inventeurs, les médecins, les hommes. A l’inverse, on s’intéressera ici à l’expérience des femmes en faisant l’hypothèse qu’il existe des différenciations dans la démarche de procréation médicalement assistée à l’image de la complexité des rapports sociaux de sexe. Effectivement, l’analyse des parcours de femmes, à partir des dossiers médicaux d’un service hospitalier spécialisé, révèle des lignes de conduite spécifiques : sont ainsi mises à jour des stratégies différentes selon la situation professionnelle, le niveau de qualification, la position vis-à-vis de l’hôpital. Avec la médicalisation croissante de notre société, le « devoir de procréation » se jouerait donc sur une scène où interviennent conjointement les rapports sociaux de sexe, la position vis-à-vis du travail, le lien avec l’institution médicale.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; angleterre; approches et analyses; corps; corps des femmes; cours; discipline; europe; france; inégalités; justice reproductive; maternité; postmodernisme; premier cycle; privilèges; procréation; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Number: 25
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Sexualité et espace public : visibilité lesbienne dans le cinéma récent - Nadeau, Chantal (Sociologie et sociétés, 1997)
Dans cet article, l'auteure démontre que la circulation et la consommation croissante des images lesbiennes dans l'espace public participent du phénomène complexe d'une culture du visible. Tout en soulignant les inévitables compromis qui découlent d'une telle négociation de la visibilité, elle retrace le potentiel culturel qu'une telle marchandisation de la " différence " représente pour les lesbiennes. L'identité et le désir lesbiens sont donc analysés ici en tant que produits représentationnels aptes à être consommés autant par les hétérosexuel.les que par les lesbiennes. Par une analyse des diverses stratégies de négociation du désir lesbien tirées de deux films populaires tant auprès d'un public hétérosexuel que gai (Gazon maudit et When Night is Falling), la critique confronte la matérialité de l'identité lesbienne au cinéma à la valeur de l'image saphique sur le marché de l'identité.
Keywords: approches et analyses; cinéma; corps; discipline; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Le sexe biologique et sa relation au sexe social - Peyre, Evelyne; Wiels, Joëlle (Les Temps modernes, 1997)
http://transidentite.free.fr/oms/peyre_wiels-les_temps_modernes1997.pdf
Keywords: anthropologie; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; lit3495; premier cycle; ressource en ligne; sciences humaines; sexe biologique; thématiques

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Engels et l'émancipation des femmes - Europe Solidaire Sans Frontières - Trat, Josette (Engels et savants révolutionnaires, 1997)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1970-1979; approches et analyses; capitalisme; classe ouvrière; corps; cours; discipline; europe; famille; france; justice sociale; marxisme; premier cycle; périodes historiques; russie; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Odile Jacob, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Première publication: 1981
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Indiana University Press, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women–menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Section: xvi, 250 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Des outils pour écrire le corps - Centre de création industrielle (Paris); Centre national d'art et de culture Georges Pompidou (Paris); de Certeau, Michel (Traverses, 1993)
Publisher: Centre Georges Pompidou
Keywords: corps; cours; discipline; lit4700; premier cycle; sciences humaines; sociologie; sofia; thématiques

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (Gallimard, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie

From mastery to analysis: Theories of gender in psychoanalytic feminism - Elliot, Patricia (Cornell University Press, 1991)
Critique des approches psychanalytiques en études féministes et de l'hystérie (Kristeva, Irigaray, Chodorow, Dinnerstein, Mitchell, Lacan, Freud) Voir le compte-rendu: Williams, C. L. (1992). [Review of From Mastery to Analysis: Theories of Gender in Psychoanalytic Feminism., by P. Elliot]. Contemporary Sociology, 21(5), 728–729. https://doi.org/10.2307/2075599
Keywords: 1900-1999; corps; cours; discipline; europe; fem1000; france; maternité; premier cycle; psychanalyse; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sexualité; thématiques